A global consensus statement on ashy dermatosis, erythema dyschromicum perstans, lichen planus pigmentosus, idiopathic eruptive macular pigmentation, and Riehl's melanosis. (3rd September 2018) - Kumarasinghe, Sujith Prasad W.; Pandya, Amit; Chandran, Veena; Rodrigues, Michelle; Dlova, Ncoza C.; Kang, Hee Young; Ramam, M.; Dayrit, Johannes F.; Goh, Boon Kee; Parsad, Davinder
Abstract: Ashy dermatosis (AD), lichen planus pigmentosus (LPP), erythema dyschromicum perstans (EDP), and idiopathic eruptive macular pigmentation are several acquired macular hyperpigmentation disorders of uncertain etiology described in literature. Most of the published studies on these disorders are not exactly comparable, as there are no clear definitions and different regions in the world describe similar conditions under different names. A consensus on the terminology of various morphologies of acquired macular pigmentation of uncertain etiology was a long‐felt need. Several meetings of pigmentary disorders experts were held to address this problem. A consensus was reached after several meetings and collation of e‐mailed questionnaire responses and e‐mail communications among the authors of publications on the above conditions. This was achieved by a global consensus forum on AD, LPP, and EDP, established after the 22nd International Pigment Cell Conference held in Singapore in 2014. Thirty‐nine experts representing 18 countries participated in the deliberations. The main focus of the deliberations was terminology of the conditions; as such, we present here the consensus statement of the forum and briefly review the available literature on the subject. We have not attempted to discuss treatment modalities in detail.